2001
DOI: 10.1046/j.1472-765x.2001.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nucleic acid amplification techniques for the assessment of bacterial viability

Abstract: Aims: The ability to determine the presence and viability status of bacteria by molecular methods could offer significant advantages to the food, environmental and health sectors, in terms of improved speed and sensitivity of detection. Methods and Results: In this study, we have assessed three amplification techniques, PCR, RT‐PCR and NASBA, for their ability to detect nucleic acid persistence in an E. coli strain following heat‐killing. NASBA offered the greatest sensitivity of the three methods tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 22 publications
2
44
1
3
Order By: Relevance
“…13 In addition, some authors noted that mRNA can persist for an extended period after cell death, precluding their use to detect bacterial viability. [14][15][16] Like PMA, ethidium bromide monoazide (EMA) is known as a DNA intercalating agent, and its use has been reported for discriminating intact from dead bacteria by PCR. [17][18][19] However, recent reports have suggested that EMA can influence intact cells as well as dead cells in some bacterial strains, and that EMA is not a suitable indicator of bacterial viability.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, some authors noted that mRNA can persist for an extended period after cell death, precluding their use to detect bacterial viability. [14][15][16] Like PMA, ethidium bromide monoazide (EMA) is known as a DNA intercalating agent, and its use has been reported for discriminating intact from dead bacteria by PCR. [17][18][19] However, recent reports have suggested that EMA can influence intact cells as well as dead cells in some bacterial strains, and that EMA is not a suitable indicator of bacterial viability.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the detection of M. leprae DNA does not indicate that the bacilli in the analyzed environmental water samples are viable. The detected DNA may originate from live or dead bacteria, or even constitute extracellular DNA 23 ; detection of bacterial DNA derived from lysis by heating followed by ultraviolet exposure has been demonstrated 24,25 .…”
Section: Tablementioning
confidence: 99%
“…The disadvantages of the assay include: i) the presence of possible contamination with genomic DNA, which often leads to false-positive results; and ii) some RNA molecules may persist in cells in a detectable form for an extended time period (about 1 h) after loss of cell viability in some specific conditions, which may lead to false positive results [101].…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%